Increasing the on-road fuel economy by trailing at a safe distance. (August 2017) - Nuszkowski, John; Smith, Harlan; McKinney, Michael; McMahan, Nicholas; Wilder, Benjamin; Boehringer, Eric; Clarkson, Blair; Littleton, Cutler; Parker, Kyle
Energy is a driving force for automotive applications. Reducing the energy demand of the vehicle is one method of increasing the fuel economy of a vehicle. Heavy-duty commercial vehicles have large frontal areas that provide large amounts of aerodynamic drag at highway speeds. Reducing the aerodynamic drag lowers the engine demand and therefore increases the fuel economy of the vehicle. This study tested the fuel economy and the front air velocity of a 10.7 m box truck trailing another box truck by distances of 3.1 times the truck length, 4.7 times the truck length, and 6.3 times the truck length at a highway speed of 28 m/s. The distance of 6.3 times the vehicle length was considered 'safe' for trailing another vehicle, whereas the distances of 3.1 times the truck length and 4.7 times the truck length were not considered safe by the United States Fire Administration. The results showed significant reductions in the air velocity in front of the trailing vehicle of 8.5%, 6.5%, and 3.8% for trailing distances of 3.1 times the vehicle length, 4.7 times the vehicle length, and 6.3 times the vehicle length respectively. The fuel economy of the trailing truck increased significantly by 7.4–8.0%, 8.2–9.0%, and 6.5%–7.7%, for trailing distances of 3.1 times the vehicle length, 4.7 times the vehicle length, and 6.3 times the vehicle length respectively. Based on a road load analysis, these fuel economy improvements indicated a reduction in the drag coefficient of the trailing vehicle of 8–10%. Therefore, a box truck trailing another box truck at a safe distance results in a reduction in the aerodynamics drag and a significant increase in the fuel economy.